A PROBLEM-BASED APPROACH TO INTEGRAL TEACHING OF MATHEMATICS - Tayirov Jamol Uktamovich (American Journals, 2023)
In given article it is considered an approach to maintenance of continuity of training to the mathematician in secondary speсialized, professional and higher educational institutions by means of systems of problems.
Keywords: problem-based approach, basic problem, system of multi-level problems, one-type problems, educational activity, levels of mastery.